Vulnerability and livelihood restoration of landless households after land acquisition: Evidence from peri-urban China. (September 2018) - Li, Chen; Wang, Mark; Song, Yanan
Abstract: The large-scale rural land acquisition projects for non-agricultural purposes has cast a long shadow on rural households' livelihoods in China. In this paper, by applying Sustainable Livelihood Framework and vulnerability approach, and based on our longitudinal study (2008–2017) on a land acquisition case in S village, Jining city, Shandong province, we discuss the dynamism of households' livelihood changes before land acquisition and in decade after land acquisition. It is found that households' different vulnerabilities and livelihood restorations in decade after land acquisition, are the results of their different capabilities of building various livelihood capitals. Another evident finding is that land acquisition as it is increasingly practiced with China's rapid urbanisation process has triggered risks to most rural households' livelihoods. The implications of the research indicate the necessity of local governments to guarantee for sustaining rural households' livelihoods after land acquisition.